Potensi Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) sebagai Bioreduktor Untuk Biosintesis Nanopartikel - Putri, Hawa Aritma Sunarko; Oktarini, Rahmi; Islamiyah, Syuaibatul; Redjeki, Sri; Yogaswara, Rachmad Ramadhan (Universitas Andalas, 2024)
One type of antioxidant that is usually found in plants such as fruit, skin, leaves, and others is flavonoids. In addition, flavonoids can be used for the formation of nanoparticles (NPs) as a bioreductor. The purpose of this study was to examine the utilization of red dragon fruit peel extract as a bioreductor in the synthesis of zinc oxide nanoparticles from zinc nitrate precursors using the biosynthesis method. Red dragon fruit peel was macerated to obtain flavonoids. Zinc nitrate was used as a precursor to make ZnO NPs. UV-VIS spectrophotometric analysis showed that the total flavonoids contained in the extract were 5.6 x 10-4 mg QE/g. By FTIR test, ZnO nanoparticles are known to contain OH groups characterized by a peak in the 3374.10 cm-1 region. XRD results show that ZnO nanoparticles have a hexagonal wurtzite shape. SEM-EDX results show that the ZnO nanoparticles formed have a size of 157-174 nm and contain the constituent composition of 69.41% zinc and 29.35% oxygen. ZnO nanoparticles have anticancer effects that can be used in anticancer drugs, which can efficiently suppress synergistic cytoxicity in leukemia cell lines under UV irradiation.